Review: Sperm cryopreservation in wild small ruminants: morphometric, endocrine and molecular basis of cryoresistance - J. Santiago-Moreno; A. Toledano-Díaz; C. Castaño; R. Velázquez; P. Bóveda; E. O'Brien; P. Peris-Frau; B. Pequeño; B. Martínez-Madrid; M.C. Esteso (Animal, 2023)
Reproductive technologies can help to protect wild ruminant species from becoming extinct. In addition, the decline in some wild game species has also raised interest in reproductive technologies to increase the number of animals that can be produced. Most biobanking efforts have focused on developing effective protocols for preserving sperm, oocytes, and embryos. Cryopreservation of sperm remains the least invasive method and the cheapest procedure for germplasm storage. Over the last few years, several reproductive biotechnologies have been developed beyond the conventional freezing of spermatozoa. These include ultra-rapid freezing techniques. Nevertheless, fertility results after artificial insemination using frozen-thawed spermatozoa are not always acceptable in wild small ruminants. Moreover, these technological efforts have met variable success related to the sample's origin (epididymal retrieved postmortem or ejaculated) and the season of sperm sample collection and storage. Epididymal sperm shows higher cryoresistance than ejaculated sperm. Changes in sperm proteome between epididymal and ejaculated sperm seem to contribute to this different cryotolerance. The role of endocrine status has been studied in some wild species to better understand the underlying mechanism of the annual variation in ruminant sperm cryoresistance. Seasonal changes in testosterone and prolactin are involved in sperm cryoresistance; sperm recovery and cryopreservation are recommended around the end of the rutting season, when good quality sperm samples can still be obtained, testosterone levels have already decreased, and prolactin concentrations remain low. The mechanisms of hormone action on sperm freezability are not well known. Still, it has been suggested that testosterone affects cell proliferation in the testis, during spermatogenesis, and membrane properties of sperm cells during their transit through the reproductive tract, which might influence their cryotolerance. Recent studies have revealed that the expression of aquaporins in the sperm cells of small wild ruminants could also be involved in the androgen-related seasonal variation of sperm cryoresistance. Along with epididymal and ejaculated spermatozoa, the cryopreservation of testicular tissue may provide a suitable source of male gametes, becoming an alternative for establishing germplasm banks when semen cannot be collected for whatever reason.